Ethical Discourse of Responsibility in The Covid19 Pandemic Humanitarian Disaster - Budiman, Arip; Gibson al-Bustomi, Ahmad (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2024)
This article aims to elaborate on how Emmanuel Levinas' discourse on the ethics of responsibility applies to the humanitarian crisis caused by the COVID-19 pandemic. Levinas offers a concrete ethical concept for addressing humanitarian issues, distinguishing himself from earlier ethical philosophy experts. The research method employed is qualitative, utilizing a literature review approach. The findings and discussion reveal that Levinas' perspective on the ethics of responsibility emphasizes concrete responsibility in encounters with the 'Face of the Other'. Furthermore, responsibility represents a form of human identity from a humanitarian perspective when facing the COVID-19 pandemic. According to Levinas, unconditional responsibility is not something we receive or a rule we agree to bind ourselves to, but rather something that exists before we make any decisions. Unconsciously, we already have unlimited responsibility towards others. The conclusion drawn is that adhering to health protocols is a concrete manifestation of Levinas' ethics of responsibility in the context of the COVID-19 pandemic, as it is oriented towards the safety of others. Levinas' ethics of responsibility is asymmetrical. The ethical discourse on responsibility discussed in this study is limited to the context of the COVID-19 pandemic, thus it has limitations in broader explanations. Although Levinas' grand ideas may not suffice to solve all the ethical issues we face, their strength lies in reminding us of the inherent nature of ethical demands that should underpin all moral theories. Levinas invites us to reconsider the essence of ethical responsibility, which transcends formal rules and agreements, towards a deeper understanding of our relationships with others